Highly Charged Ruthenium(II) Polypyridyl Complexes as Effective Photosensitizer in Photodynamic Therapy. Issue 45 (2nd July 2019) - Conti, Luca; Bencini, Andrea; Ferrante, Camilla; Gellini, Cristina; Paoli, Paolo; Parri, Matteo; Pietraperzia, Giangaetano; Valtancoli, Barbara; Giorgi, Claudia
Abstract: A comparative study between two novel, highly water soluble, ruthenium(II) polypyridyl complexes, [Ru(phen)2 L ′] and [Ru(phen)2 Cu(II)L ′] (L and L ‐Cu II ), containing the polyaazamacrocyclic unit 4, 4′‐(2, 5, 8, 11, 14‐pentaaza[15])‐2, 2′‐bipyridilophane (L ′), is herein reported. L and L ‐Cu II interact with calf‐thymus DNA and efficiently cleave DNA plasmid when light‐activated. They also possess great penetration abilities and photo‐induced biological activities, evaluated on an A375 human melanoma cell line, with L ‐Cu II being the most effective. Our study highlights the key role of the Fenton active Cu II center within the macrocycle framework, that would play a synergistic role with light activation in the formation of cytotoxic ROS species. Based on these results, an optimal design of Ru II polypyridyl systems featuring specific Cu II ‐chelating polyamine units could represent a suitable strategy for the development of novel and effective photosensitizers in photodynamic therapy. Abstract : Charged for Therapy : Novel Ru II and Ru II /Cu II mixed polypyridyl complexes featuring different light‐activated mechanisms, singlet oxygen generation, and Fenton‐like oxidative pathways were studied as possible photosensitizers for photodynamic therapy.